If it's not what You are looking for type in the equation solver your own equation and let us solve it.
6t+12=3(t-7)+6t
We move all terms to the left:
6t+12-(3(t-7)+6t)=0
We calculate terms in parentheses: -(3(t-7)+6t), so:We get rid of parentheses
3(t-7)+6t
We add all the numbers together, and all the variables
6t+3(t-7)
We multiply parentheses
6t+3t-21
We add all the numbers together, and all the variables
9t-21
Back to the equation:
-(9t-21)
6t-9t+21+12=0
We add all the numbers together, and all the variables
-3t+33=0
We move all terms containing t to the left, all other terms to the right
-3t=-33
t=-33/-3
t=+11
| 3/6=h/12 | | 22=k+20 | | 5.50+75x=3.10+1.35x | | x-5/6=-4 | | 2(x-34)=(-15) | | 4(2b-6)+11=6b+13 | | -4x+1073=17x+1010 | | 12+x–8=7x+5–5x | | 6x-2(2+8x)=10+4 | | 5y-9=6y-4 | | (1/2)k=3.2 | | 1.03^x=36 | | 4/3g+1/6=7/6 | | -5a+36=16 | | x+1/6= | | -6y=45 | | -30=5t | | (y-22)+y=72 | | 5=a-3.2 | | x^2-14x-12=4 | | -x^2+1=12 | | 9-5x=1-2 | | -0,66x^2-4,6x+6,56=0 | | -0,66x^2-4,6x+8,56=0 | | 100/12.5=v | | n−7=49 | | 3(2+x)-(2+x)=14 | | 3x-(2+x)=14 | | 6+6x-(2+x)=14 | | −2x+5=12 | | 1.7x0.5=5.25 | | 28,392.31-x=11,356.21 |